Neo-Scholastic Conception of the Object of Philosophy in Lithuania - Rinkevičienė, Rūta (Problemos, 1990)
The article deals with the differentiation of Neo-Scholastic philosophy in Lithuania. The philosophy was declaring the Thomistic conception of the object of philosophy. The author of the paper demonstrates how two models of philosophy were formed, namely, that of orthodox philosophy (Thomistic) and that of unorthodox philosophy (oriented towards spiritualism). The first was postulating as an object of philosophy the problem of the relation between the natural world and the divine reality. The second was accentuating the relation between man and God as the central problem of philosophy.